INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH - Nur Ahyani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
In order to establish the character of the students it is necessary to integrate character education in all subjects to realize Indonesian men of noble character. In practice, national education today, there is a discrepancy between the ideals of national education to social reality that happened,  student disputes, misuse of drugs. These phenomena may be they are due among other factors teachers, curriculum and learning tools. History is one of the subjects taught in high school history courses function directed to the formation of personality. If subjects associated with the history and character education delivered by attractive, then the student will not feel bored, even raised nationalism and have a noble character.